A 55-Day-Old Female Infant Infected With 2019 Novel Coronavirus Disease: Presenting With Pneumonia, Liver Injury, and Heart Damage. (17th March 2020) - Cui, Yuxia; Tian, Maolu; Huang, Dong; Wang, Xike; Huang, Yuying; Fan, Li; Wang, Liang; Chen, Yun; Liu, Wenpu; Zhang, Kai; Wu, Yue; Yang, Zhenzhong; et al.
Abstract: Background: Previous studies on the pneumonia outbreak caused by the 2019 novel coronavirus disease (COVID-19) were mainly based on information from adult populations. Limited data are available for children with COVID-19, especially for infected infants. Methods: We report a 55-day-old case with COVID-19 confirmed in China and describe the identification, diagnosis, clinical course, and treatment of the patient, including the disease progression from day 7 to day 11 of illness. Results: This case highlights that children with COVID-19 can also present with multiple organ damage and rapid disease changes. Conclusions: When managing such infant patients with COVID-19, frequent and careful clinical monitoring is essential. Abstract : Data about infants infected with novel coronavirus disease (COVID-19) are scarce. Herein, we report a 55-day-old case who presented with COVID-19 pneumonia. The exposure, symptoms, laboratory indicators, and hospitalization are described in detail.